Feeding and Draining Vessel Ligation with Sclerotherapy of High Flow Arteriovenous Malformations in the Head and Neck - Felixberto D. Ayahao (Philippine Journal of Otolaryngology Head and Neck Surgery, 2014)
High flow arteriovenous malformations (AVMs) are infiltrative, invading tissue planes and structures and may be life threatening when they bleed.1 They have a feeding artery and an anomalous capillary bed shunting blood from the arterial system to the venous system.1 The present trend of management of small AVMs is surgical excision with a high success rate. The problematic cases are diffuse AVMs infiltrating structures that render them impossible to totally extirpate surgically without causing much blood loss and tissue damage. The mainstay of management is embolization, surgical resection and reconstruction.2 Ligation or proximal embolization (alone) of feeding vessels should never be done because such maneuvers result in rapid recruitment of new vessels from adjacent arteries to supply the AVM nidus.2 Incomplete surgical excision definitely leads to recurrences, making this type of AVM very difficult to manage.